Association Between Perceived Levels of Stress and Self-Reported Food Preferences Among Males and Females: A Stated Preference Approach Based on the China Health and Nutrition Survey - Fahui Yang; Fahui Yang; Ruonan Li; Xiaojian Ren; Bing Cao; Bing Cao; Xiao Gao; Xiao Gao (Frontiers Media S.A., 2022)
ObjectiveStress is a major public health challenge and is associated with undesirable eating behavior. This cross-sectional study aimed to explore whether there is an association between perceived level of stress and food preference among Chinese adults.Study DesignPerceived level of stress was measured using the Chinese version of the 14-item Perceived Stress Scale, whereas self-reported food preferences were investigated by means of five food classification questions, including questions regarding the consumption of fast food, salty snacks, fruit, vegetables, and soft/sugary drinks.MethodsThe data were collected from the 2015 China Health and Nutrition Survey. Information of 8,216 adults (≥18 years) on perceived level of stress, self-reported food preferences, and other important covariates was available and analyzed.ResultsPerceived level of stress was negatively associated with a preference for fruit (β = −0.58, 95% CI: −0.81 to −0.34, p < 0.0001) and vegetables (β = −1.13, 95% CI: −1.41 to −0.85, p < 0.0001), while it was positively associated with a preference for fast food (β = 0.36, 95% CI: 0.08-0.64, p = 0.011) and soft/sugary drinks (β = 0.48, 95% CI: 0.30-0.66, p < 0.0001) after adjusting for potential confounders. No association between a preference for salty snacks and perceived level of stress was found in either men or women.ConclusionsThe present population-based study reported strong associations between perceived level of stress and self-reported food preferences among Chinese adults. Sex differences related to this association were also worthy of attention.